Woven into the air– Dance as a practice towards ecologically and socially just communities - Turkki, Nella (My University, 2020)
This research aims to examine methods of an artistic-pedagogical process and their potential for working with a diverse group. The theoretical reference point is EcoJustice education, a framework for ecologically and socially just pedagogy. The two research questions are: (1) How can my artistic-pedagogical methods as a dance pedagogue open a dialogue about climate crises, fostering more ecologically and socially just awareness in diverse groups? Moreover, (2) how do my pedagogical methods utilised in the given process of ILMA relate to the EcoJustice framework? The basis of this research is the artistic process of the devised dance performance ILMA (Finnish for “air”) which is the artistic part of my artistic-pedagogical thesis. ILMA is a dance performance about climate emotions and nature relationships in today’s world, and it premiered at the Zodiak New Dance Centre in Helsinki, Finland on 7th of March 2020. The working group of ILMA consisted of a diverse group of people from various backgrounds and aged between 14–84 years, a scenographer, light designer and musician and myself as the facilitator and director. The 13 performers of ILMA were found through an open call and workshop that handled the emotions related to climate change through dialogue, autobiographical writing and dance improvisation. The pedagogical dance practices turned out to foster connection and a sense of belonging in the group, that allowed the participants to reflect on their narratives concerning the bigger picture of our society and the ecosystem in a supportive atmosphere. Through dance improvisation, sensing exercises and embodiment practices, the participants found possibilities to express climate emotions in creative ways of working creating movement material and scenes for the ILMA performance. The analysis of the movement-based methods was framed by three main elements of my pedagogy; diversity, connection, and belonging. From the EcoJustice point of view, dance performance projects like ILMA can also foster the connectedness and feeling of hope due to the practices of recognition and connection. EcoJustice education can also work as a framework for ecologically and socially aware dance pedagogy offering space for imagination, feeling of interconnectedness, and questioning the modern destructive behaviour. To further develop the methods utilised in ILMA, an initial framework of a Pedagogy of (Be)longing was created. The pedagogy is based on the bodily practices that foster diverse ways of knowing. With open dialogue and autobiographical practises it also advances the connection to one’s own body, the others and the more-than-human world – and that way a sense of belonging. The Pedagogy of (Be)longing will be further developed in my future studies and practices.
Keywords: Dance pedagogy; Dance education; tanssitaide; Critical dance pedagogy; Ecojustice education; Ecological crises; arts-based research; Embodied learning; Embodied knowledge; Climate emotions; Eco-anxiety; Art education.; Dance.; Dance improvisation; Climate change.; Ecology and environment; Environment; Air.; Autobiographical.; taidepedagogiikka; tanssi; taidekasvatus; kriittinen pedagogiikka; improvisointi; ilmastonmuutokset; ympäristövaikutukset; taiteellinen tutkimus; ilma; omaelämäkerrallisuus; konstpedagogik; dans; konstfostran; kritisk pedagogik; improvisering; klimatförändringar; miljöeffekter; konstnärlig forskning; luft; självbiografiska drag; fi=tanssinopettaja|sv=danspedagogik|en=Dance Pedagogy|